Frontal aslant tract in the non-dominant hemisphere: A systematic review of anatomy, functions, and surgical applications - Gallet, Clémentine; Clavreul, Anne; Bernard, Florian; Menei, Philippe; Lemée, Jean-Michel (Frontiers in Neuroanatomy, 2022)
Knowledge of both the spatial organization and functions of white-matter fiber tracts is steadily increasing. We report here the anatomy and functions of the frontal aslant tract (FAT) in the non-dominant hemisphere (usually the right hemisphere). Despite the structural symmetry between the right and left FAT, these two tracts seem to display functional asymmetry, with several brain functions in common, but others, such as visuospatial and social cognition, music processing, shifting attention or working memory, more exclusively associated with the right FAT. Further studies are required to determine whether damage to the right FAT causes permanent cognitive impairment. Such studies will constitute the best means of testing whether this tract is a critical pathway that must be taken into account during neurosurgical procedures and the essential tasks to be incorporated into intraoperative monitoring during awake craniotomy.